APLIKASI PRESENSI SISWA BERBASIS WEB DAN QR - CODE PADA MADRASAH ALIYAH MAZRO’ATUL HUDA KARANGANYAR DEMAK - Zuhri, Haikal (Universitas Muria Kudus, 2023)
Madrasah Aliyah Mazro'atul Huda Karanganyar Demak is an upper secondary educational institution founded by the Mazro'atul Huda Karanganyar Foundation, Demak. Every activity that requires information about students will require attendance, the attendance process is still manual, namely by writing in the attendance book which takes a long time and there are often problems in conducting data recap. With this problem, an application is made using a QR-Code and based on the Website. The method used uses Waterfall through several stages such as data collection, problem identification, system analysis, system design, system development, system testing, system implementation. This website-based application is built using 3 main components, namely PHP as a programming language, PhpMyAdmin as a Database Server and Web-Cam or External Camera as a QR-Code reader application. Web-based attendance application, it is hoped that data can be stored in the database, students do not have to wait long for attendance and can speed up data recapitulation and minimize absentee fraud.